2000
DOI: 10.1007/s000240050002
|View full text |Cite
|
Sign up to set email alerts
|

About the Efficiency of Numerical 1-D and 2-D Modelling of Site Effects in Basin Structures

Abstract: In the present study we compare results obtained from experimental estimates of local site amplification effects with those from numerical modelling using four different techniques. We benefit from an extremely precise knowledge of the near-surface structure and experimental estimates of the local amplification factors which are determined from seismic weak-motion data recorded by a dense array across a sedimentary basin at a European test-site in Northern Greece. The possibilities and limitations of the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…In it they found that the amplification levels for frequencies higher than 1 Hz is better modeled. Following the conclusions in [1] and this study, it could be inferred that these high amplifications at the edges can be assessed more reliably by a combination of a more realistic: geometry of the near-surface soil-as the one shown in model II, and of the incident radiation on the rock basement (to be performed in future works).…”
Section: Multi-layered Structure (Model Ii)supporting
confidence: 55%
See 4 more Smart Citations
“…In it they found that the amplification levels for frequencies higher than 1 Hz is better modeled. Following the conclusions in [1] and this study, it could be inferred that these high amplifications at the edges can be assessed more reliably by a combination of a more realistic: geometry of the near-surface soil-as the one shown in model II, and of the incident radiation on the rock basement (to be performed in future works).…”
Section: Multi-layered Structure (Model Ii)supporting
confidence: 55%
“…Notice the amplification at the edges of the basin (STC, STE) for frequencies higher than 1.5 Hz. This last specific characteristic of the seismic response has been underestimated in other numerical studies using a standard finite-difference method [1], where the authors pointed out that it could be due to several reasons concerning the simplification of models: the nonexisting surface weathered layer in their model, some neglected thin layers, the smoothing of the inhomogeneous fault zone, more complex 3D effects,... In the same work the authors performed a more complex computation of the response of the basin applying a hybrid method to account for a more realistic incident wave field.…”
Section: Multi-layered Structure (Model Ii)mentioning
confidence: 94%
See 3 more Smart Citations